An asymmetric A–DA′D–π-A type non-fullerene acceptor for high-performance organic solar cells. Issue 7 (29th November 2021) - Zhang, Zhe; Li, Dawei; Zhang, Huarui; Ma, Xueqin; Chen, Ya-Nan; Zhang, Andong; Xu, Xiaoyun; Liu, Yahui; Ma, Zaifei; Bo, Zhishan
Abstract : Utilizing the symmetry-breaking and π-bridge-extending strategy, three non-fullerene acceptors with DA′D core unit and electron-withdrawing unit are designed and synthesized via changing the alkoxy-substituted thiophene bridge unit. Abstract : Under the guidance of a symmetry-breaking and π-bridge-extending strategy, three asymmetric and symmetric non-fullerene acceptors (L1, L2, and L3 ) with DA′D core units and two 2-(5, 6-difluoro-3-oxo-2, 3-dihydro-1 H -inden-1-ylidene)malononitrile electron-withdrawing units (A) have been designed and synthesized via changing the alkoxy-substituted thiophene bridge unit. The asymmetric A–DA′D–π-A-type non-fullerene acceptor (NFA) L2 displays much improved solubility and a slightly larger molar absorption coefficient than its symmetric counterparts (L1 and L3 ). In addition, blend film based on the asymmetric NFA L2 shows suitable nanoscale phase morphology and much higher and more balanced hole and electron mobilities. Hence, compared with L1 - and L3 -based organic solar cells (OSCs), optimal L2 -based devices can deliver a high power-conversion efficiency (PCE) of 14.06% with simultaneously enhanced current density and fill factor values. Our study indicates that a combined symmetry-breaking and π-bridge-extending strategy is powerful for the design of high-performance NFAs.